Measurement of electric potential difference on trees - Koppán, András (Acta Biologica Szegediensis, 2002)
Electrical potential differences have been continuously recorded since 1997 between electrodes inserted in sixteen selected sites of the trunk of a Turkey oak (Quercus cerris L.) and in the ground. The measured electric potential difference data have a characteristic sinusoidal daily variation. The annual fluctuation of the mean daily amplitudes of these diurnal variations has at least two maxima per year. We found a remarkable correlation between electric potential differences (EPD), the water potential of air and sap flux density data. It means that the EPD follows the variations of the sap flow intensity.